The Relationship Between Trainers' Personality, Their Work Environments, and Job Satisfaction: A Test of Holland's Theory of Vocational Choice - Sta. Maria, Rebecca Fatima (1993)
The assumption that congruence between personality and work environment results in job satisfaction is fundamental to vocational theory. The research study tested the relationship between person-environment congruence and job satisfaction as assessed by Holand's model of vocational preference on as ample of 94 trainers at the National Institute of Public Administration (INTAN). The research study applied the Environmental Assessment Technique (EAT) to obtain the occupation code for the INTAN work environment. Subsequently, the Vocational Preference Inventory (VPI) was used to obtain the personality profile of the trainers. The relationship between personality and environment was examined. The research study then investigated whether or not there was a significant difference in job satisfaction bet ween trainers who are congruent with the work environment and trainers who are incongruent with the work environment.